2018
DOI: 10.1002/jee.20225
|View full text |Cite|
|
Sign up to set email alerts
|

A Multimodal Exploration of Engineering Students' Emotions and Electrodermal Activity in Design Activities

Abstract: Background This exploratory study uses multimodal approaches to explore undergraduate student engagement via topic emotions and electrodermal activity (EDA) in different engineering design method activities and with different instructional delivery formats (e.g., lecture vs. active learning). Purpose/Hypothesis The goal of this research is to improve our understanding of how students respond, via engagement, to their engineering design activities during class. This study hypothesizes that students would experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 77 publications
2
33
0
1
Order By: Relevance
“…The EDA accounts for a strong emotion but the correlation with its valence (quality of emotion, positive or negative) is unclear. In their study, Villanueva et al (2018) looked at engineering students' emotions in different learning situations (passive and active learning) and workshop topics (problem statement, generation of ideas, selection of design solutions, prototyping, presenting design solution). This study showed an increase in EDA for active and collaborative learning compared to passive learning.…”
Section: Eda: Measuring Learning In Design and Engagement In Design Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDA accounts for a strong emotion but the correlation with its valence (quality of emotion, positive or negative) is unclear. In their study, Villanueva et al (2018) looked at engineering students' emotions in different learning situations (passive and active learning) and workshop topics (problem statement, generation of ideas, selection of design solutions, prototyping, presenting design solution). This study showed an increase in EDA for active and collaborative learning compared to passive learning.…”
Section: Eda: Measuring Learning In Design and Engagement In Design Tmentioning
confidence: 99%
“…Learning design in the studio implies social and collaborative learning, where tutors adapt their comments to students based on their perceived abilities. Obtaining data on students' engagement and emotions during a course points out the effect of teaching methods on students (Villanueva et al 2018). The design studio pedagogy is partly implicit, and tutors with professional backgrounds tend to teach without any pedagogical training.…”
Section: Feedback To Design Educatorsmentioning
confidence: 99%
“…Such a focus is related to Pekrun's (2006) concept of shame as an achievement emotion or “emotions tied directly to achievement activities or achievement outcomes” (p. 317), which has characterized the framing of how shame has been studied in educational research (Paoloni et al, 2014; Tempelaar et al, 2012; Villavicencio, 2011). While we are not aware of engineering education studies that have explicitly investigated shame, we do note that extant research on emotions in engineering domains are aligned with Pekrun's (2006) framework of achievement emotions (Atiq, 2018; Kellam et al, 2018; Villanueva et al, 2018).…”
Section: Professional Shamementioning
confidence: 93%
“…This is also true for research in engineering education: the few existing studies on emotions in engineering education rely on individual and cognitivist perspectives on emotions. The focus of that research is on emotions as individual competencies or experiences, such as empathy [6], shame [7], and frustration [8] (see also [9,10]). In the broader educational literature, however, there is today an emerging body of research from discourse analytic perspectives that explores emotions as social and cultural phenomena.…”
Section: Introductionmentioning
confidence: 99%